The effects of the community-driven development concept on the success implementation of flood management construction in the Ciujung Basin - Wibowo, Yudistira; Suroso, Agus; Hidayat, Acep (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
The flood-prone area in Serang Regency ranges to 22,617.49 hectares (ha), the trigger factor for flooding in Serang Regency is the high rainfall ranging from 200 mm – 400 mm in the rainy season. The local government of Serang Regency handles floods with non-structural methods. The method applied is flood handling with the concept of community-driven development. CDD is a community-based development concept with a process of resource development and direct decision-making by community groups. The Serang district government has succeeded in minimizing flooding with the concept of CDD in the Ciujung watershed area, it needs to be improved in terms of human resources, community participation, socio-culture, quality-quantity and budget. Analysis of the effect of the application of the CDD concept on the success rate of flood control construction using qualitative descriptive methods. The success rate of implementing the CDD concept in the implementation of flood control construction is influenced by socio-cultural aspects with a dominance rate of 28,476%. The benefits of this research are to increase the application of non-structural methods with the concept of CDD and become a reference by stakeholders in the implementation of community-based development, for that it is necessary to reorganize the planning, implementation and maintenance stages based on local wisdom and community aspirations.